In vitro evaluation of novel titania‐containing borate bioactive glass scaffolds. Issue 2 (26th June 2020) - Shafaghi, Romina; Rodriguez, Omar; Wren, Anthony W.; Chiu, Loraine; Schemitsch, Emil H.; Zalzal, Paul; Waldman, Stephen D.; Papini, Marcello; Towler, Mark R.
Abstract: Titanium‐containing borate bioactive glass scaffolds (0, 5, 15, and 20 mol %, identified as BRT0, BRT1, BRT3, and BRT4) with a microstructure similar to that of human trabecular bone were prepared and evaluated in vitro for potential bone loss applications in revision total knee arthroplasty (rTKA). Methyl thiazolyl tetrazolium (MTT) cell viability assays of scaffold ion release extracts revealed that BRT0 scaffolds (0 mol % titanium) inhibited cell proliferation and activity at day 14. At day 30, all scaffold extracts decreased cell proliferation and activity significantly. However, live/dead cell assay results demonstrated that degradation products from all the scaffolds had no inhibitory effect on cell viability. Significant bactericidal efficacies of BRT3 extracts against Escherishia coli (Gram‐negative) and BRT1 extracts against Staphylococcus aureus and Staphylococcus epidermidis (both Gram‐positive bacteria) were demonstrated. Finally, evaluation of the cell/bioactive glass surface interactions showed well‐spread cells on the surface of the BRT3 glass discs and BRT1 and BRT3 scaffolds, when compared to BRT0 and BRT4 scaffolds. The results indicate that by changing the Ti 4+ :B 3+ ratio, the ion release and consequently cell proliferation could be improved. in vitro results in this study demonstrate that BRT3 scaffolds could be a promising candidate for addressing bone loss in rTKAs; however, in vivo studies would be required to evaluate the effect of a dynamic environment on the cell and tissue response to the fabricated scaffolds.